1994
DOI: 10.1111/j.1476-5381.1994.tb16187.x
|View full text |Cite
|
Sign up to set email alerts
|

Infection by HIV‐1 blocked by binding of dextrin 2‐sulphate to the cell surface of activated human peripheral blood mononuclear cells and cultured T‐cells

Abstract: Structural analogues of a sulphated polysaccharide, dextrin sulphate, were synthesized and tested for their ability to block infection by HIV‐1. Using the T‐cell lines, C8166 and HPB‐ALL, and the laboratory adapted strains of HIV‐1.MN, HIV‐1.IIIb and HIV‐1.RF, dextrin 2‐sulphate (D2S) combined the best combination of high anti‐HIV‐1 activity (95% inhibitory concentration (IC95) = 230 nM) and low anticoagulant activity. It also blocked infection of activated peripheral blood mononuclear (PBMN) cells by five pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 42 publications
1
21
0
1
Order By: Relevance
“…Although histones are commonly associated with DNA, the presence of histones on cell surfaces has been described in both eukaryotic and prokaryotic cells. In particular, histone H2B is present on the cell surface of leukocytes (29), T cells (30)(31)(32)(33)(34), B cells (35), and a human lung carcinoma cell line (36). Extracellular histones can stimulate lymphoid cell proliferation and Ig synthesis (37).…”
Section: Discussionmentioning
confidence: 99%
“…Although histones are commonly associated with DNA, the presence of histones on cell surfaces has been described in both eukaryotic and prokaryotic cells. In particular, histone H2B is present on the cell surface of leukocytes (29), T cells (30)(31)(32)(33)(34), B cells (35), and a human lung carcinoma cell line (36). Extracellular histones can stimulate lymphoid cell proliferation and Ig synthesis (37).…”
Section: Discussionmentioning
confidence: 99%
“…Fucoidan and dextrin 2-sulfate had selectively indices (SI) of 200. Dextrin 2-sulfate has undergone other human tests (Shaunak et al, 1994(Shaunak et al, , 1998Sta!ord et al, 1997).…”
Section: Spermicidal Activity Of Sulfated Polysaccharides Fucoidan mentioning
confidence: 99%
“…This compound also inhibits the infection of T-cells by the human immunodeficiency virus type 1 in vitro (13), although its mechanism of action has not been elucidated. Nevertheless, we have demonstrated that D2S binds to histones H2A, H2B, H3, and H4, all of which are located on the plasma membrane of activated T-cells (14).…”
mentioning
confidence: 99%